Being Ram Dass - Ram Dass (Sounds True, 2021)
"Professor Richard Alpert's star fell fast. To the dismay of his wealthy Boston family, he got fired from Harvard over experimental use of psychedelics with his psychology students. In 1967, he traveled to India to lick his wounds and find himself. And he did, at Neem Karoli Baba's ashram, in a direct encounter with unconditional, unlimited divine love. He returned to America as Baba Ram Dass, countercultural activist for expanded human consciousness. As a spiritual guide, at the bedside of the dying, and as a stroke survivor, he has always been ahead of his time, pulling the world along behind him. The author of over a dozen books, he now shares for the very first time the full story of how his life of service intersected with an era of profound cultural upheaval. From the details of his groundbreaking research in psychedelics to his bumpy path to becoming a spiritual icon, from his struggles with his sexual identity to what it was like to find out in his late 70s that he was a father and grandfather, Ram Dass traces the pivotal points of his life against the backdrop of a mind opened by drugs, and a heart opened by a guru. Ram Dass brought America yoga, the use of psychedelics in psychotherapy, and a revolution in how we relate to death and dying. He has opened the door to the most important and healthiest conversations about the heart and mind in our culture. With this book, he opens his heart and mind to us"--